Lithuanian Tatars Manuscripts Written in Arabic Script from a Private Collection: New Discoveries - Miškinienė, Galina (Slavistica Vilnensis, 2020)
At the turn of the 20th and the 21st centuries, more and more attention is being paid to the written heritage of Lithuanian Tatars. From 1997 to 2020 seven catalogues of Lithuanian Tatars manuscripts were published. These catalogues describe the Lithuanian Tatars manuscripts kept in state institutions, museums, archives, as well as in private collections of various countries. The largest collections of manuscripts are stored in Belarus and Lithuania. The emergence of such catalogues is an excellent basis for further comparative studies.In 2020 the author of this article managed to get acquainted with a new collection of manuscripts stored in a private collection. Five manuscripts were reviewed and analyzed during this research. All of them perfectly represent the main genres of Lithuanian Tatars manuscripts heritage, such as kitabs, semi-kitabs, hamails, and tefsirs. The manuscripts are dated to the end of the 19th – the beginning of the 20th centuries. A detailed description of these manuscripts is presented in this article.
Keywords: Lithuanian Tatars; kitabs; manuscripts; description; private collection of manuscripts